E-STUDENT WORKSHEET BASED ON QR CODE ASSEMBLR EDU: THE DEVELOPMENT OF GEOGRAPHY LEARNING SOURCE IN THE ERA OF DIGITALIZATION - Karunia Puji Hastuti; Deasy Arisanty; Ahmad Ilham Masful Fani; Nevy Farista Aristin; Aswin Nur Saputra; Dharmono Dharmono (GeoEco, 2026)
One of the challenges in using student worksheets lies in their limited visual appeal, minimal interactivity, unclear instructions, and lack of technological integration, all of which fail to promote higher-order thinking skills and consequently reduce the effectiveness of learning and its relevance to contemporary students’ needs. This study aims to develop electronic student worksheets (e-student worksheets) based on the Assemblr Edu QR code that are valid and practical for students. This research employs the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. The selection of the Research and Development (R&D) method was based on the need to design, validate, and produce a feasible digital learning product that aligns with the demands of technological innovation in the geography learning process. The study involved 184 Grade X students of SMAN 8 Banjarmasin, with data collected through observations and questionnaires. The research instruments included validation and product-effectiveness sheets. Validation was conducted by experts in materials, language, and media/learning technology, while teachers and students implemented effectiveness testing. The developed QR Code–based Assemblr Edu LKPD obtained material validation of 90.90% (very feasible), language validation of 95% (very feasible), and media/technology validation of 95.83% (very feasible). Product effectiveness reached 95.29% from teachers (very feasible) and 78.02% from students (feasible). These results indicate that the QR Code–based Assemblr Edu LKPD is highly appropriate for use in learning, particularly in geography instruction.